Electron time-of-flight: a new tool in β-decay spectroscopy - Roick, Christoph; Dubbers, Dirk; Schmidt, Ulrich (Physical review, 2018)
We show that electron time-of-flight can be a useful tool in β-decay spectroscopy, even in the energy range up to 700 keV relevant for neutron β decay. As a first application, we use electron time-of-flight measurements for the precise calibration of an electron detector.
Gesehen am 10.04.2019